Produção de hidrogênio por fermentação anaeóbia: enrequecimento nutricional e influência da luminosidade - Souza, Isadora Torres (2017)
Hydrogen is considered one of the most promising energy carriersdue its high energy conversion efficiency. In this way, the intensive investigation of the sustainable production of hydrogen attracts more and more researchers. In the present work, the potential hydrogen producer by the bacteria Enterobacter aerogenes and Enterobacter cloacae was studied for for different parameters. The batch fermentations evaluated the influence of light and sources of carbon, glucose and whey permeate. In addition, the influence of inert gases nitrogen and argon in the light fermentation for hydrogen producing bacteria was also verified. The tests were carried out in 50 mL reactors during 108 hours. In the case of E. aerogenes the substrate was the variable that most influenced the fermentation. The volume of hydrogen obtained using glucose as substrate was higher than the fermentation with cheese whey permeate, and the best fermentation conditions of the respective substrates generated 3.18 and 0.86. It was also verified that the influence of the light got positive results, being the fermentation yield with glucose in the presence and absence of light of 0.94 and 1.51 mols H2/mol of hexose, respectively. However, the influence of E. cloacae in the substrate and illumination was less expressive. In the dark fermentation the yields for glucose and lactose were 1.60 and 1.39 mols H2/mol of hexose, respectively. While in the light fermentation the yield was equivalent to glucose and 33% higher for lactose when compared to the dark situation. About the inert gas, only the E. cloacae showed improvement in the results. The yield in the presence of argon gas and was higher by 47% and 37% for glucose and lactose, respectively, when compared to the same condition with nitrogen gas. Verifying better results for E. cloacae, the microorganism was evaluated in the hybrid system condition in a 50 mL reactor. The effluent generated in the dark fermentation was used in the light phase, which generated a yield of 2.01 mols H2/mol hexose. The increase in fermentation scale for a stirred tank reactor of 1.5 L was proposed for E. cloacae. In this system, the dark fermentation happened for 432 hours while the biogas production was verified, obtaining a maximum yield of 110.09 mmol H2/L·day and yield of 2.16 mols H2 mol/mol hexose. In general, E.cloacae showed to be more promising for the production of hydrogen using both glucose and lactose as carbon source, and the results of this microorganism were optimized in the presence of inert gas argon.